Efficient ESL-Event-to-SQL translation - Phucharoen N. (2014)
Expressive Stream Language-Event (ESL-Event), which is based on the traditional SQL, is a language developed for streaming data management. It can handle the data streams and temporal event queries effectively. However, it has yet to be implemented commercially. In this paper, we propose an efficient ESL-Event-to-SQL translation. Since the SQL language can be used widely on the traditional DBMSs. Thus, our proposed work allows the users to leverage the features of the ESL-Event on the current systems with no effort. Our approach firstly parses an ESL-Event statement into the intermediate representation, the parse tree. Subsequently, the tree is converted to the SQL-syntax-complied parse tree, in which the semantic of all the ESL-Event features is well preserved and implemented efficiently. Once the tree is traversed, the SQL statement is generated. From the experiment results, our work is highly efficient. © Springer-Verlag 2013.